Gradual Increase of FcγRIIIa/CD16a Expression and Shift toward IFN-γ Secretion during Differentiation of CD56dim Natural Killer Cells - Lajoie, Laurie; Congy-Jolivet, Nicolas; Bolzec, Armelle; Thibault, Gilles (Frontiers in Immunology, 2017)
Natural killer (NK) cell effector functions include cytotoxicity and secretion of cytokines such as interferon-γ (IFN-γ). The immature CD56bright subset of human NK cells lacks expression of FcγRIIIa/CD16a, one of the low-affinity immunoglobulin G receptors, or exhibits low-density expression (CD56brightCD16-/dim) and produces IFN-γ in response to cytokine stimulation, whereas the mature CD56dimCD16+subset is the most cytotoxic one. A further differentiation/maturation of the latter subset according to the gradual loss of NKG2A and/or gain of KIR2DL (CD158a and CD158b) has been demonstrated and the ability to produce IFN-γ in response to activating receptor (ARs) co-engagement is gradually acquired during terminal differentiation. In the course of flow cytometry analysis of CD56dim NK cells, we noted a substantial intra-individual heterogeneity of expression of FcγRIIIa, which is the sole AR whose engagement is sufficient to induce substantial cytotoxicity/degranulation and/or cytokine synthesis in CD56dim cells. FcRIIIa is unique among ARs: it doesn’t require the co-engagement of other ARs to induce substantial cytotoxicity or cytokine synthesis in CD56dim cells. We therefore investigated whether individual differentiation/maturation of polyclonal CD56dim NK cells defined by expression of NKG2A/KIR2DL is related to FcγRIIIa expression and to the heterogeneity of NK cell responses upon FcγRIIIa engagement. When we analyzed unstimulated CD56dim cells by increasing level of FcγRIIIa expression, we found that the proportion of the more differentiated CD158a,h+ and/or CD158b,j+ cells and that of the less differentiated NKG2A+cells gradually increased and decreased, respectively. FcγRIIIa engagement by using plate-bound murine anti-CD16 monoclonal antibody (mAb) or rituximab or trastuzumab (two therapeutic mAbs), resulted in donor-dependent partial segregation of IFN-γ-producing and/or degranulating CD56dim cells. Importantly, the proportion of CD158a,h/b,j+ cells and that of NKG2A+ cells was increased and decreased respectively in the former cells IFN-γ-producing cells, whereas these proportions were poorly modified in the latter cellsdegranulating cells. Similar results were observed after engagement of ARs by a combination of mAbs targeting NKG2D, NKp30, NKp46 and 2B4. Thus, the gradual increase of FcγRIIIa expression is an important feature of the differentiation/maturation of CD56dim cells and this differentiation/maturation is associated with a shift in functionality toward IFN-γ secretion observed upon both FcγRIIIa-dependent and FcγRIIIa-independent stimulation. The